Moderasi Beragama Melalui Pemujaan Hindu-Islam Di Pura Keramat Desa Adat Seseh Kabupaten Badung - Putu Diantika; Gusti Nyoman Mastini (Kamaya: Jurnal Ilmu Agama, 2023)
The implementation of religious moderation is the key to creating harmony and tolerance at the local, national and global levels. One of the holy places in Bali which symbolizes the concept of religious moderation is the Sacred Temple. The worship performed at the Keramat Temple involves two different religions, namely Hinduism and Islam. Historically, the existence of the Sacred Temple is marked by the presence of the sacred tomb of one of the Wali Pitu in Bali named Pangeran Mas Sepuh, after a long journey in spreading his teachings, after the death of Pangeran Mas Sepuh tomb was worshiped by Hindus and Muslims. This study aims to describe the attitude of religious moderation contained in the worship performed by Hindu-Muslims at the Keramat Temple, so that there is no wrong perception of the Keramat Temple, which can lead to religious conflicts. The method used in this research is qualitative, where data collection uses observation, interviews, and literature studies. So that the results obtained, namely: Religious moderation carried out at the Keramat Temple, namely in Hindu-Islamic worship occurs in a balanced way and there is no conflict, can foster a sense of unity and oneness in the midst of different beliefs. This is in line with the commitment of the nation that needs to be carried out by the community and the millennial generation in relation to Indonesian multiculturalism and all its positive aspects. The form of worship at the Keramat Temple is carried out by Hindus and Muslims in their respective ways and rituals, Hindus perform prayers by offering offerings to the graves and shrines of the Keramat Temple. Meanwhile, Muslims worship focused on the tomb in the Keramat Temple by reciting the holy verses of the Al-Quran. The implications of worship at the Keramat Temple are divided into four aspects, namely socio-religious implications, cultural implications, economic implications and religious implications.